2020
DOI: 10.1002/jsde.12402
|View full text |Cite
|
Sign up to set email alerts
|

Modulation in Aggregation Behavior of Cationic Surfactant in Presence of Fluoroquinolone Drug: A Physicochemical Approach

Abstract: Measurements of density, speed of sound, conductivity, and fluorescence spectroscopy have been carried out to study the interactions between cationic surfactant cetyltrimethylammonium bromide in an aqueous solution of the fluoroquinolone drug at different concentrations and temperatures. Volumetric and compressibility parameters, such as apparent molar volumes (V φ ), isentropic compressibility (κ s ), and apparent molar isentropic compressibility (κ φ, s ), have been obtained from density and speed of sound. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…Figure 5 and Figures S8 and S9 show that, as alkyl chain length increases, the normalΔHm* value decreases, indicating that the higher the normalΔHm* value, the less stable micelles form. In addition, the value for compensation temperature, T c , falls within the well‐established 284–310 K temperature range for different alkyl ammonium bromide surfactants (Chauhan & Pathania, 2018; Pathania & Chauhan, 2020a, 2020b).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Figure 5 and Figures S8 and S9 show that, as alkyl chain length increases, the normalΔHm* value decreases, indicating that the higher the normalΔHm* value, the less stable micelles form. In addition, the value for compensation temperature, T c , falls within the well‐established 284–310 K temperature range for different alkyl ammonium bromide surfactants (Chauhan & Pathania, 2018; Pathania & Chauhan, 2020a, 2020b).…”
Section: Resultssupporting
confidence: 68%
“…It has been found that the hydrophobes of tetraalkyl ammonium salt are known to penetrate into the micellar core of the surfactant and have a tendency to make the micelle shrink and act as spacers between the surfactant head groups (Esan et al, 2015). Apart from this, in molten state, these salts also behave as ionic liquids and in this capacity, various multiapproach applications concentrating on the change in the behavior of aqueous surfactant solution with the incorporation of additives like electrolytes or drugs have been published in recent years (Pathania & Chauhan, 2020b; Tanwar et al, 2021). Therefore, in the present work, the changes in the physicochemical properties of CTAB in aqueous solution upon addition of R 4 N + Br − at different temperatures have been investigated by using conductometric technique and calculating various thermodynamic parameters which are useful to know about the thermal stability of these ternary systems.…”
Section: Introductionmentioning
confidence: 99%
“…The spontaneity of process is portrayed analogous to sign of normalΔGmo values. The negative normalΔGmo values, divulges that the CTAB and DTAB molecules undergo spontaneous aggregation in aqueous solutions of amikacin sulphate (Pathania and Chauhan, 2020).…”
Section: Resultsmentioning
confidence: 99%